Consumer preferences in air travel : an application of conjoint analysis. - Leoh, Chay Hoon. (2008)
Examines the most important attribute perceived by both short-haul and long-haul travellers using conjoint analysis and these two groups were compared based on the values attached to the attributes. Price trade-off analysis was performed. Cluster analysis technique was applied to group consumers with similar preferences to uncover underlying demographic profiles.